Aspergillus nidulans pyrE and pyrF - A Aleksenko; H N Arst Jr; A J Clutterbuck (Fungal Genetics Reports, 2000)
Sequencing of a gene cloned by complementation of a pyr mutant in Glasgow strain G190 shows this mutant to be pyrE, encoding dihydroorotate dehydrogenase. This discovery necessitates a revision of the genetic map derived from crosses with this strain.